Impact of a nutrient-rich health bar intervention on health and cognitive performance among children and adolescents in the B40 community in Gombak - Nurul Auni Mohd Noor; Noor Yuslida Hazahari; Norshazila Shahidan; Azura Amid; Noor Soffalina Sofian Seng; Eko Susanto (IIUM Press, 2026)
Non-Indexed Publication